Dataset for: On-farm testing of 11 pre-released elite clones in five provinces of Mozambique, 2024 - Makunde, G.S.; Gonzaga, L.; Ssali, R.T.; Yada, B.; Mtonga, A.; Serenje, G.; Odiyo, O.; Musundire, L. (2025)
CIP Mozambique tested 11 pre-released clones under on-farm for multi-stakeholder validation across five provinces (Niassa, Nampula, Zambezia, Manica and Inhambane) ensuring representation of diverse environments and farmer conditions. Five districts were selected in each province for on-farm trialing and a total of 170 farmers successfully established the trials. The TRICOT design was the experimental design of choice. Most agricultural actors, including farmers, extension officers and other local government representatives were involved in the setting up of trials and their assessment. Farmer and other stakeholders feedback on performance clones will be utilized and incorporated into decisions of variety release and genetic gains in farmers’ fields will be calculated. The validation system strengthened the selection and adoption of new varieties, integrating farmer needs and gender considerations into breeding advancements.